Respuesta :

Nayefx

Answer:

[tex] \displaystyle 7[/tex]

Step-by-step explanation:

first thing I assume by f~¹ you meant [tex]f^{-1}[/tex] however

we want to find +3x-3 for the given condition. with the composite function condition we can do so

Finding the inverse of f(x):

[tex] \displaystyle f(x) = \sqrt{ax + 1} [/tex]

substitute y for f(x):

[tex] \displaystyle y= \sqrt{ax + 1} [/tex]

interchange:

[tex] \displaystyle x= \sqrt{ay + 1} [/tex]

square both sides:

[tex] \displaystyle ay + 1 = {x}^{2} [/tex]

cancel 1 from both sides:

[tex] \displaystyle ay = {x}^{2} - 1[/tex]

divide both sides by a:

[tex] \displaystyle y = \frac{{x}^{2} - 1 }{a}[/tex]

substitute f^-1 for y:

[tex] \displaystyle f ^{ - 1} (x) = \frac{{x}^{2} - 1 }{a}[/tex]

finding the inverse of g(x):

[tex] \displaystyle g(x) = \frac{x + 1}{x} [/tex]

substitute y for g(x)

[tex] \displaystyle y= \frac{x + 1}{x}[/tex]

interchange:

[tex] \displaystyle \frac{y + 1}{y} =x[/tex]

cross multiplication

[tex] \displaystyle y + 1= xy[/tex]

cancel 1 from both sides

[tex] \displaystyle y - xy= - 1[/tex]

factor out y:

[tex] \displaystyle y(1 - x)= - 1[/tex]

divide both sides by 1-x:

[tex] \displaystyle y= - \frac{1}{ 1 - x}[/tex]

substitute g^-1 for y:

[tex] \displaystyle g ^{ - 1} (x)= - \frac{1}{ 1 - x}[/tex]

remember that

[tex] \displaystyle (f \circ g)x = f(g(x))[/tex]

therefore we obtain:

[tex] \rm \displaystyle (f ^{ - 1} \circ g ^{ - 1} ) (3) = \frac{{ \bigg(- \dfrac{1}{1 - 3} } \bigg)^{2} - 1 }{a}[/tex]

since (f~¹•g~¹)(3)=-⅜ thus substitute:

[tex] \rm \displaystyle \frac{{ \bigg(- \dfrac{1}{1 - 3} } \bigg)^{2} - 1 }{a} = - \frac{3}{8} [/tex]

simplify parentheses:

[tex] \rm \displaystyle \frac{{ \bigg( \dfrac{1}{2} } \bigg)^{2} - 1 }{a} = - \frac{3}{8} [/tex]

simplify square:

[tex] \rm \displaystyle \frac{{ \dfrac{1}{4} } - 1 }{a} = - \frac{3}{8} [/tex]

simplify substraction:

[tex] \rm \displaystyle \frac{ - \dfrac{3}{4} }{ a}= - \frac{3}{8} [/tex]

simplify complex fraction:

[tex]\rm \displaystyle - \dfrac{3}{4a} = - \frac{3}{8}[/tex]

get rid of - sign:

[tex]\rm \displaystyle \dfrac{3}{4a} = \frac{3}{8}[/tex]

divide both sides by 3:

[tex]\rm \displaystyle \dfrac{1}{4a} = \frac{1}{8}[/tex]

cross multiplication:

[tex]\rm \displaystyle 4a= 8[/tex]

divide both sides by 4:

[tex]\rm \displaystyle \boxed{ a= 2}[/tex]

as we want to find +3a-3 substitute the got value of a:

[tex] \displaystyle {2}^{2} + 3.2 - 3[/tex]

simplify square:

[tex] \displaystyle 4 + 3.2 - 3[/tex]

simplify multiplication:

[tex] \displaystyle 4 +6 - 3[/tex]

simplify addition:

[tex] \displaystyle 10 - 3[/tex]

simplify substraction:

[tex] \displaystyle 7[/tex]

and we are done!